GOOD DISTRIBUTION PRACTICE: MODERNISATION OF THE MEDICINES DISTRIBUTION SYSTEM IN RUSSIA - E. V. Yakovleva (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article describes the main stages of introduction of the Good Distribution Practice (GDP) in Russia following the adoption of new laws making it mandatory for wholesalers to comply with requirements for storage and transportation of medicinal products. The article compares the regulatory requirements of the European Union, Eurasian Economic Commission and the Russian Federation for GDP system development by entities involved in medicines circulation. It highlights the main activities that help a wholesaler create an efficient GDP system. The key role in the implementation of GDP principles is played by the director of the company and the employee in charge. The article analyses the risk-oriented approach that the Federal Service for Surveillance in Healthcare relies upon when supervising wholesalers of medicinal products. It was demonstrated that the compliance of a product with efficacy and safety criteria can only be assured if GDP standards are met.